THE IMPLEMENTATION OF SCIENTIFIC APPROACH TO ENCHANCE STUDENTS’ SPEAKING ABILITY AT SMAN 1 TAKALAR - Maulana, Awal; syam, Ummi khaerati; Baso, Farisha Andi (FKIP Unismuh Makassar, 2024)
This research aimed at finding out whether or not the implementation of scientific approach can improve the students’ speaking ability in term of accuracy (vocabulary) and smoothness at the SMAN 1 Takalar. This research was conducted through pre-experimental method. The population of this research consisted of one class of the ten grade and the sample of the research took IPA 4 class which consisted of 23 students in academic year 2022/2023. In collecting the data, the researcher gave a speaking test, the speaking test help into two steps, there were pre-test and post-test. The findings of this research showed that the mean score in pre-test in term of vocabulary was 53.30 and the post-test was 76.56. The mean score in pre-test in term smoothness was 51.86 and the post-test was 80.04 and the total result of vocabulary and smoothness in pre-test was 100.13 and the post-test was 160.08 with the improvement percentage in their speaking after being taught through scientific approach was 59.87% hence the students’ ability in speaking became better than before. Based on the result above, the researcher concluded that there was significant improvement of the students’ speaking ability by using scientific approach in SMAN 1 Takalar.